Immediate impacts of COVID-19 on the aquaculture value chain in Ghana - Ragasa, Catherine; Amewu, Sena; Asante, Seth (International Food Policy Research Institute, 2021)
Ghana’s aquaculture sector is among the recent success stories of fast-growing agricultural value chains in Africa south of the Sahara. The sector has also shown its vulnerability, with the infectious spleen and kidney necrosis virus spreading through tilapia farms in Lake Volta in late 2018. The global COVID-19 human pandemic reached Ghana in early 2020, affecting the sector directly and indirectly. Using a value chain approach, phone interviews were conducted with 369 small-scale fish farmers in six major producing regions, with 12 other value chain actors, and with 423 consumers in the capital, Accra, to assess the impact of COVID-19 on the sector. All value chain actors interviewed reported being affected directly by COVID-19 related restrictions on movement and indirectly by reduced demand for tilapia because of closures in the tourism and hospitality industries, important consumers of fresh tilapia. The crisis has reduced incomes for most actors along the aquaculture value chain and is anticipated to reduce future production. Most fish farmers surveyed were affected by disruptions in input and output markets. Two-thirds of the sample farmers were growing fish and 6 percent were harvesting when the COVID-19 crisis hit. Fifty-four percent of those growing fish experienced difficulties in accessing inputs – mainly fish feeds. Of those harvesting during the crisis, most experienced difficulty in selling their fish mainly because of low demand from buyers, lower tilapia prices, and higher transportation costs than before COVID-19. Income losses among fish farmers, including from other sources, such as crop farming, wage employment, and other own businesses, limits the funds that they have available to finance fish farming operations or to invest in future production capacity. Likewise, reduced incomes and purchasing power of consumers is causing a sharp decline in demand for fish.